Gestión de ventas en la “Boutique Juana Aldaz” de la ciudad de Babahoyo. - Torres Robelli, Angie Celine (2022)
Within the present case study which was prepared with the purpose of analyzing the sales management of the boutique Juana Aldaz in the city of Babahoyo, so it does not manage to be competitive in the Babahoyense market, due to a series of shortcomings that have been found around the marketing of clothing products offered in the establishment. The method of methodological approach was used which allowed to collect information on the variable of the case study with the theme Sales management of the boutique Juana Aldaz also conducted a field work in this was able to collect information on the current state in the the establishment is located and thus learn about the sales management employed by this and its collaborators, was used to collect this inquiry, the interview form is addressed to the owner and survey form made to customers of the establishment. The owner of the boutique Juana Aldaz indicated that through comparisons in levels of sales, productivity and creativity of the workers with whom it counts in the local, also through the profitability it obtains, said that the factors that affect their sales find that they can be improved and recognized that it has to apply new tools. Among the factors that affect sales in the establishment Juana Aldaz was obtained firsthand by the owner that the incursion into social networks where you can publicize their products is the factor that most influences low levels of sales periodically.